The papillomacular fold in posterior microphthalmos - Nowilaty, Sawsan (2013)
FREE ARVO Annual Meeting Abstract | June 2013 The Papillomacular Fold in Posterior Microphthalmos: New Insights Based on Novel Spectral-Domain Optical Coherence Tomography Findings Sawsan Nowilaty; Ahmed Mousa; Nicola Ghazi Author Affiliations & Notes Investigative Ophthalmology & Visual Science June 2013, Vol.54, 5819. doi: SHARE E-MAIL FACEBOOK TWITTER GOOGLE DIGG DELICIOUS CITEULIKE TUMBLR STUMBLEUPON TOOLS ALERTS GET CITATION GET PERMISSIONS Abstract Purpose: To characterize using spectral-domain optical coherence tomography (SD-OCT), the internal structure of the papillomacular fold in posterior microphthalmos (PM) and analyze the posterior pole curvature in PM and its relationship to the axial length (AL) and the papillomacular fold features and pathogenesis. Methods: Forty PM eyes (20 patients) and 70 control eyes (35 subjects) underwent AL biometry (IOLMaster) and macular SD-OCT (Spectralis). SD-OCT features analyzed included the papillomacular neurosensory retinal fold’s internal structure, height and protrusion, and a novel parameter termed the “posterior pole curvature index (PPCI)” measured along the vertical and horizontal meridians. The relationship of the PPCI to the papillomacular fold height and AL, as well as to the PPCI of controls was analyzed. Results: All papillomacular folds, regardless of their height, were horizontal and invariably partial thickness sparing the photoreceptor layer, inner segment/outer segment junction, external limiting membrane, and outer nuclear layer. The retinal stratification was preserved within the fold. There was no foveal depression. Papillomacular folds harbored clinically-invisible inner nuclear layer cysts in 50%, additional clinically-visible ganglion cell layer cysts in 35% and surface corrugations with prominent vitreous in 65% of cases. PM eyes had notably larger vertical and horizontal PPCIs than controls (vPPCI mean 173 vs. 13μ; hPPCI 118 vs. 15μ, p < 0.0001 for both). Moreover, in all PM eyes, but not in controls, the vertical PPCI was notably larger than the horizontal PPCI (mean difference of 55μ, p <0.0001) and correlated strongly with inverse AL (R= -0.71, p <0.0001) and papillomacular fold height and protrusion (R= 0.68, p <0.0001). Papillomacular fold height and protrusion also correlated strongly with inverse AL (R = -0.62, p <0.0001). Conclusions: The papillomacular fold in posterior microphthalmos is consistently partial thickness, horizontally oriented with predictable internal and surface anatomical features. The posterior pole curvature in PM is invariably steep, particularly along the vertical meridian, and correlates strongly with the inverse axial length and the papillomacular fold height and protrusion. These findings may offer novel clues for the pathogenesis and consistent horizontal orientation of the papillomacular fold.